(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The development of contemporary architecture demonstrates an increasingly intensive degree of interdisciplinary intervention arising from environmental, technological, social, cultural, and artificial intelligence-related issues. Although this tendency is frequently understood as a form of progress, in practice it has generated a phenomenon of increasingly blurred architectural boundaries, in which dwelling space as the formal object of architecture is gradually displaced by external indicators such as technical performance, data, or symbolic representation. This research aims to reconceptualize the boundaries of architecture through a reaffirmation of the relationship between architectural ontology, disciplinary development, and interdisciplinary contribution. This study employs a theoretical–conceptual analytical method grounded in reconstructive synthesis of the thoughts of Aristotle, Vitruvius, Norberg-Schulz, Hillier, Broadbent, and Salura. The analysis is conducted progressively through three principal stages: the reaffirmation of architectural ontology, the formulation of disciplinary development, and the determination of the liminal domain as a testing zone for external contributions. Within this process, the Core Ontology of Architecture is operationalized through the concept of the Minimum Threshold of Spatial Structure (MTSS) as an ontological testing instrument for determining the minimum condition of inhabitable space. The findings indicate that the boundaries of architecture may be formulated as a layered structure consisting of: the Ontology of Architecture as the principle of embodied human dwelling within spatial configuration; the Core Ontology of Architecture as the minimum condition of inhabitable space; the MTSS as the minimum ontological threshold; the Core Discipline of Architecture as the mechanism for the physical realization of space; the Spectrum of Architectural Disciplines as the enrichment and expansion of dwelling; and the liminal domain as a testing zone for interdisciplinary contributions. This structure demonstrates that the boundaries of architecture are relational and hierarchical in nature, not rigid separations, but rather orientative mechanisms that maintain the ontological consistency of architecture amidst interdisciplinary openness. This research also positions the Architectural Property–Composition Epistemic Framework (APCEF/KEPKA) as an epistemic mechanism that ensures every architectural claim can be traced and verified through the relationships among spatial configuration, function, experience, and meaning. Accordingly, this study contributes to formulating the integration of ontology, ontological threshold, and epistemic mechanism in architecture as a coherent conceptual structure. Theoretically, this research reinforces the position of architecture as a discipline rooted in inhabitable space. Methodologically, it provides an orientative framework for evaluating the position of research and design practice within interdisciplinary contexts. These findings demonstrate that architecture does not lose its relevance because it possesses ontological boundaries; rather, it becomes vulnerable to weakening when such boundaries are neither recognized nor conceptually operationalized.